Construction of Climate of Social Affection in Realizing the Noble Morals of Youth (Phenomenology Study in Medan Johor Kota Medan District) - Raudatus Shafa, Lahmuddin Lubis, Candra Wijaya (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: This research aims to find solutions to the problem of the formation of juvenile morals in Medan Johor sub-district, which includes: Construction of a climate of social affection in the formation of the ideal adolescent noble morals. This research uses qualitative research methods with phenomenological approaches. The results of this study analysis showed that the social climate in the formation of adolescent morals in Medan Johor sub-district was categorized as lack of affection and did not yet have a climate pattern of social affection in the formation of specific adolescent morals in both families, schools and the general public. Iklim social affection plays a big role in the formation of juvenile morals in Medan Johor Subdistrict. Factors that construct a climate of social affection in the formation of adolescent morals in the form of foundations of values, principles, structures and instruments of climate social affection, have not been fully contained in the process of forming juvenile morals in Medan Johor sub-district. These climate factors of social affection are actually available but have not been optimally empowered in the process of adolescent moral formation. The first factor, the basis of the value of climate social affection is the value of faith in God Almighty. The second factor of the principle of climate of social affection consists of cooperation, competence, willpower, excitement, appreciation, honesty, discipline, empathy, knowledge and ethics of decency. The third factor, the climate structure of social affection consists of believing in God, charitable charity, advising each other in truth and advising each other in patience. While the fourth factor of climate instruments of social affection in the formation of adolescent morals is the same as the elements in education that have been implemented universally, namely goals, educators, learners, subject matter, learning methods, infrastructure facilities, evaluation and learning atmosphere. The findings obtained in the study became the basis for submitting recommendations to authority holders and stakeholders in the city of Medan and the Government of North Sumatra Province to: All components of society can synergize the power of focus on efforts to build climate construction social affection in the formation of juvenile morals.